STUDENTS’ ABILITY IN ANALYZING AMBIGUOUS PERSONAL REFERENCE IN WOMEN’S MURDER CLUB: THE TRIAL NOVEL - Masykur Rauf; Reski Amanda (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
This research discussed students’ ability in analysing ambiguous reference in written text. The objectives of this research were to find out students’ ability, and the way of the seventh-semester students of English and Literature Department (2016) in analysing the given extracts. The Researchers used quantitative and qualitative methods for collecting and analysing data. The data source was the seventh-semester students of English and Literature Department (2016). The Researchers used paper test (close-ended and open-ended question) as the instrument to get the data. As the procedure of collecting data, the Researchers gave the students the test and the instruction to answer the test. The Researchers then collected the paper after the students answered the tests. The Researchers used Halliday and Hasan’s reference theory which focusing on personal reference. Based on the findings and discussion, the Researchers found that 1 student possessed excellent ability, 2 students got good ability, 5 students belonged to fair ability, and 2 students obtained poor ability. As the conclusion, the seventh-semester student of English and Literature Department (2016) had fair ability (67.09) in analysing ambiguous personal references. It was proved by their mean score through the paper test (multiple choice). And the Researchers also concluded that analysed the given extracts by 3 ways. Those were by the context, good sense, and guessing. It was proved by their answers got through open-ended questionnaire.